Comunicação e memória nas redes da criação de Juraci Dórea - Lôbo, Carolina Cerqueira (2011)
The research suggests a study of the creation processes by the Bahian plastic artist and architect Juraci Dórea who has dedicated himself to the arts since the 1960s. The study has as object one of his works, the multi faceted Projeto Terra (Project Earth). With the creative basis in paintings and sculptures produced and fixed in the hinterland, the TERRA is also composed of photos, audio recordings, videos, books and a diary that register not only the works , but also the presence and testimony of native people at the exhibition sites. The goal of this paper is to discuss the relations of interaction and communication of the Projeto Terra with the geographical and socio- cultural environments where it is inserted, highlighting the diversity of the resources used for its documentary register in a collection of multimedia character. Such goal reflects in the assumption that the work is boosted by a force of expression that seeks to unite memory and tradition with renewal and invention and especially by a desire of communication that reaches from the aesthetic to the anthropological, from discourse to dialogue, from representation to self-exposition, forming a complex network. Thus, the methodological approach adopted is set in a case study based on the perspective of the critique of a semiotic base process that discusses the creation as a network in construction